Environmental responsibility in the function of achieving corporate sustainability - Krstić, Bojan; Jovanović, Sonja; Tasić, Milica (Hotel and Tourism Management, 2014)
At the time of strong and frequent changes affecting the socio-economic system and bringing into question the survival of the entire natural system, the development of green economy is seen as a progress in the development of a modern economy and society. The concept of green economy thereby helps in implementing and achieving goals of sustainable development, which means that the green economy must comprise all of the "three pillars of sustainability": the social, economic and environmental. The green economy is not a state but a process of transformation and constant dynamic improvement, which can also be realized at the corporate level through environmentally responsible way of doing business, or through doing "green business". This corporate move requires full engagement of the entire management team from all corporate levels and systematic guidance through all stages of its implementation: planning, control and its future improvements. Only using such an approach in establishing elements of environmental responsibility in daily operations of the company can ensure the sustainability of its development, or in other words achieve its corporate sustainability.